Time and band limiting for matrix valued functions: an integral and a commuting differential operator. (9th January 2017) - Grünbaum, F A; Pacharoni, I; Zurrián, I
Abstract: The problem of recovering a signal of finite duration from a piece of its Fourier transform was solved at Bell Labs in the 1960's, by exploiting a 'miracle': a certain naturally appearing integral operator commutes with an explicit differential one. Here we show that this same miracle holds in a matrix valued version of the same problem.